Kinematic calculation and plotting of lifting height and speed of the tangential cam pusher using MATHCAD program - Yu. P. Makushev; T. A. Polyakova; L. Yu. Volkova; V. V. Ryndin (Омский научный вестник)
The article shows the design features of tangential cams with a rounded top, provides a method for determining the lifting height and speed of the pusher when the roller is rolling in a straight line and in contact with the actual profile of the cam. The formulas for the kinematic calculation of the tangential cam are refined taking into account the radius of the initial circumference of the shaft, the radius of the rounding of the cam tip and the value of the radius of the pusher roller. Calculations are given to determine the stroke and speed of the pusher when the roller is rolling on the sections of the straight and arc-shaped surface of tangential cams with a radius of rounding of 6 and 10 mm. Formulas are proposed for determining the lift of the pusher in the rolling section of the roller along the radius of the cam tip at a constant coefficient λ = 1 and λ = 1,5. Using the Mathcad program calculations are performed and combined graphs of the pusher lift and the change in its speed are constructed for two types of tangential cams.